The Liquidus in Cu–O–CaO System at Metallic Copper Saturation up to 1698 K. Issue 1 (10th October 2014) - Hamuyuni, Joseph; Hellstén, Niko; Akdogan, Guven; Taskinen, Pekka; Vanderah, T. A.
<x xml:space="preserve">Abstract</x> We present experimental results for the liquidus of the pseudo binary system Cu2O–CaO at metallic copper saturation up to 1698 K in steps of 25 K. In this study, we quantified the liquidus (on the CaO side of the binary) by the equilibration, quench, and analysis technique, with Cu2O, CaO, and Cu as the only primary crystalline phases. Experiments were conducted in an atmosphere of pure argon up to the critical temperature (1618 K) in the Cu–O system. Above this temperature, experiments were performed at a fixed oxygen pressure of (PO2 = 1.01 kPa). Equilibrated specimens were quenched in ice‐cold water. We then quantified the liquid chemical compositions by means of energy‐dispersive X‐ray spectroscopy and electron probe micro‐analyzer. Results from this study reveal that below the critical point, some previous studies have overestimated CaO solubility amounts in the molten phase of the system, by up to 4.35 wt% CaO. Thermodynamic modeling of systems containing this binary should therefore also account for this variance.